2023
DOI: 10.1097/md.0000000000034378
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary melanomas: A literature review

Adina Patricia Apostu,
Loredana Ungureanu,
Salomea Ruth Halmagyi
et al.

Abstract: Survival rates for melanoma have increased in recent years, a higher number of patients survive after diagnosis, and, therefore, are at an increased risk of developing second primary melanoma. The aim of this literature review is to identify and integrate the incidence rates and other characteristics of multiple primary melanomas. A total of 36 independent studies were included in this review. The incidence of multiple primary melanomas reported ranged from 1.1% to 20.4%. Synchronous melanomas account for 5% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(217 reference statements)
0
2
0
Order By: Relevance
“…Given the fact that cases of multiple primary melanoma do not benefit from specific therapeutic resources other than those destined for the tumor with the greatest Breslow index, and, therefore, with the most advanced stage of disease, periodic full skin examinations and lifelong specialty follow-up exams are crucial for the early detection of a subsequent primary melanoma lesion, as well as for the identification of potential metastases [1]. Wide local surgical excision of any second or consequent primary melanoma is the mandatory step required for diagnostic confirmation and staging and it may be performed in a safer manner and with better survival outcomes inversely proportional to the tumoral thickness [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that cases of multiple primary melanoma do not benefit from specific therapeutic resources other than those destined for the tumor with the greatest Breslow index, and, therefore, with the most advanced stage of disease, periodic full skin examinations and lifelong specialty follow-up exams are crucial for the early detection of a subsequent primary melanoma lesion, as well as for the identification of potential metastases [1]. Wide local surgical excision of any second or consequent primary melanoma is the mandatory step required for diagnostic confirmation and staging and it may be performed in a safer manner and with better survival outcomes inversely proportional to the tumoral thickness [20].…”
Section: Discussionmentioning
confidence: 99%
“…The CDKN2A gene, functioning as a tumor suppressor, undergoes inactivation through homozygous deletions situated in the 9p21 chromosomal region, which leads to cellular proliferation and disruption of pro-apoptotic pathways. It has been demonstrated that these genetic changes are linked to cases of multiple primary melanomas (MPMs) and the maximum number of primaries reported in a patient was 13, with a mean per individual ranging from 2.1 to 2.8 [1]. Individuals diagnosed with melanoma face an elevated risk of developing additional primary melanomas and the occurrence of MPM is recognized in 0.2 to 8.6% of patients initially diagnosed with a single melanoma, who have been reported to experience an overall poorer survival outcome [2].…”
Section: Introductionmentioning
confidence: 99%